Reporting trends of right-sided hyperplastic and sessile serrated polyps in a large teaching hospital over a 4-year period (2009-2012) - Gill, P; Wang, L; Bailey, A; East, J; Leedham, S; Chetty, R (2013)
Aim An audit of serrated polyps diagnosed over a 4-year period: 2009 to 2012 was undertaken to ascertain the reporting trends of sessile serrated polyps (SSP). Methods All right sided hyperplastic polyps (HP) proximal to the splenic flexure and all polyps designated SSP were retrieved from the study period. Three pathologists blinded to the original diagnosis re-examined the slides. Recent American College of Gastroenterology guidelines for the diagnosis of SSP was utilised. Results No cases of SSP were diagnosed in 2009. In 2010, 32 right-sided cases were encountered, 83 confirmed in 2011 and 134 confirmed in 2012. The vast majority of these were right-sided. With regards to right-sided HP that were re-classified as SSP the data is as follows: 20 of 66 in 2009 (30%); 58 of 91 in 2010 (64%); 42 of 106 (40%) in 2011 and 69 of 206 in 2012 (33%). Conclusions This study has demonstrated an almost exponential increase in the diagnosis of SSP over a 4-year period. In addition, 30 to 64% of right-sided HP were re-classified as SSP over the 4-year period suggesting that greater awareness of the diagnostic criteria for SSP is required. SSP is an important precursor lesion in the serrated pathway of colorectal cancer. Its recognition is important for surveillance and therapeutic strategies.